PANEL RESPONSE: FISCAL POLICY - Fiscal Policy and Redistribution in Ireland - Nolan, Brian (The Economic and Social Review, 2025)
I was delighted to contribute to this conference in honour of Patrick Honohan and to recognise and celebrate his outstanding contribution to Irish economics and economic policy. We have been very fortunate to have had him over the last half-century, not only as a scholar, thinker and analyst but also playing such a crucial “hands on” role in navigating the financial crisis. I am also fortunate personally to have had him as a good friend since we worked together in the Central Bank all the way back in the 1970s and subsequently for his time in the ESRI in the 1990s. Framed against the very helpful paper to the conference by Barra Roantree on fiscal policy and redistribution in Ireland (Roantree, 2025), my aim here is to complement and elaborate on it by highlighting a number of important points about inequality, redistribution and income growth in Ireland that are not as widely appreciated as they should be.